Spatial distribution of tourist resources in Drina national park - Nezirović, Senada; Avdić, Belma (Journal for Geography, 2019)
The natural features of the protected areas offer such attractions that in many countries became the framework of tourism and recreation development. Tourism in protected areas promotes nature and contributes to raising the level of knowledge and ecological awareness and is important for the economy and employment of the local population. The aim of this paper is identification and valorisation of tourism resources in the Drina National Park. The most important economic activity in the Drina National Park, which should be developed and improved in the next period is tourism, as the main driver of development. Therefore the focus of this work is on proposals for the improvement of existing and finding new tourist facilities in Drina National park, in order to enrich the tourist offer. For this reason, the possibilities of building educational, cycling and hiking trails as well as adequate promotion and protection of the cultural and historical heritage that would be self-sustainable were analyzed, enabling the use of such facilities and sites as new resources for the development of tourism.This paper describes the concept of protection and management goals, as well as the advantages and disadvantages that need to be improved in the future and which reduce the competitiveness of the Drina National Park.